The SALCOR framework: A transformative approach to employee well-being - Nthabeleng Mdhluli; Sonja Grobler (SA Journal of Industrial Psychology)
Orientation: The well-being of employees is essential for the sustainability of an organisation; however, current models frequently neglect the significant connection between individual resources and organisational culture. The SALCOR framework integrates the salutogenic model with conservation of resources (COR) theory to effectively address these limitations through a comprehensive, resilience-focused approach.